Processo cultural e subjetividade humana : significações de uma oficina de educação estética - Astolfi, Maria Luciane Gobbo dos Santos (2007)
The present study it is a qualitative research, centered in a simbiossinérgica cosmovisão and inventiveness, that it intends to promote quarrels concerning the cultural process, of the aesthetic education, the art and the human being. The problematic one developed from the questioning on which the significações of a workshop of aesthetic education in the singularity of adults of determined cultural context. The general objective was to work with a group of adult people of the city gaucho of Ipiranga do Sul field of activity of the research , for, by means of the aesthetic experience, to look for to observe the relations between itself and the particularities of each one, relating them with the cultural environment the one that belong and to the culture established between the group, its underlying attitudes in same relation itself and its world. The understanding and quarrel of the results, under the method of the transtextual reading of images, developed for Ormezzano (2001), are based on the images produced for the participants in the last meeting, when they had answered to the following question: What it meant for me to have participated of the workshop of Aesthetic Education . The transtextual reading of images provided to the participants to approach the significação of a workshop of aesthetic education, and its implications at the lived moment. The findings constructed throughout the inquiry had as well as demonstrated that through the activities proposals, it can be observed cultural and subjective factors of each integrant one of the group, aspects of the culture established between them